Descriptive Study of Self-Disclosure through Facebook of Psychology Students, Public Health Faculty of Nusa Cendana University - Christine Desi Adonia Bansae; Dian Lestari Anakaka; Indra Yohanes Kiling (Lontar : Journal of Community Health, 2020)
Self-disclosure is very important in a relationship or communication. Communication can be done through various media, both print, and other media. Along with the development of times and technology, self-disclosure can also be done either directly or indirectly. Indirectly, it can be done in various social media such as Instagram, WhatsApp, Twitter, and one of the popular media, namely Facebook. This study aims to describe the level of self-disclosure of psychology students of the faculty of public health on Facebook based on the characteristics of gender, age, place of residence, semester. This type of research uses a quantitative descriptive study. The data collection technique uses a scale that is distributed online via a google form. The research participants were 222 psychology students. The results showed that students had a low level of self-disclosure in the form of a low quantity seen from the empirical mean that was smaller than the hypothetical mean (23.7 <24), and the empirical mean valence was smaller than the hypothetical mean (18.2 <21), the hypothetical mean of accuracy is greater (14.9 <15), then broadness has a smaller empirical mean (17.2 <18) as well as smaller empirical mean familiarity (18.3 <24). Both male and female participants have low levels of self-disclosure. Participants aged 18-20 years (early adolescents) had the highest level of self-disclosure compared to the 21-22 age group (middle adolescents) and 23-24 years old (late adolescents). Participants who live at home and in boarding houses have low levels of self-disclosure. Participants who occupy semesters II, VI and VII have a lower level of self-disclosure compared to participants in semesters IV, X and XII.